Anti-oxidant Potentiality of Guduchi (Tinospora cordifolia) Supplemented to Lactating Buffaloes under Field Conditions - Devasena, B.; Rani, K. Sudha; Adilaxmamma, K. (International Journal of Bio-resource and Stress Management, 2026)
The study was conducted during the hot dry season (ambient temperature 40–43°C, relative humidity 13–43%, THI 78.7–82.4) under field conditions in the year 2021 at Chapadu, in the Kadapa district of Andhra Pradesh to study the antioxidant and anti-stress potential of Tinospora cordifolia (Guduchi/Amruta) against solar radiation-induced heat stress in early lactating Murrah buffaloes. Twenty buffaloes were randomly assigned to control and treatment groups; the treatment group received 120 g day-1 of dried T. cordifolia plant powder mixed into the concentrate for 30 days. Milk production and composition, somatic cell count (SCC), and erythrocytic oxidative stress parameters-including superoxide dismutase (SOD), reduced glutathione (GSH), and lipid peroxidation (LPO) were measured on days 10, 20, and 30. Supplementation of T. cordifolia significantly (p<0.01) increased average daily milk yield by 14.27% and 4% fat-corrected milk (FCM) yield by 18.94% compared to the control. Milk fat, SNF, protein, and total solids were significantly improved, while SCC was markedly reduced (130×10³ vs. 256×10³ cells ml-1, p<0.01), indicating enhanced udder health. Antioxidant profiling revealed that SOD activity decreased by 5.44% and 19.78% on days 20 and 30, respectively, and GSH levels declined by 17.0% and 29.5%, reflecting a reduced oxidative burden. LPO was significantly lower in the treatment group throughout the study, with a 31.8% reduction on day 30 (p<0.05). These results demonstrated that T. cordifolia supplementation mitigated heat-induced oxidative stress, stabilized cellular redox balance, and improved milk yield and quality in buffaloes. Thus, T. cordifolia represented a practical phytogenic strategy to enhance antioxidant defenses and dairy productivity under thermal stress conditions.